2021
DOI: 10.3389/fimmu.2021.776879
|View full text |Cite
|
Sign up to set email alerts
|

The Macrophage Reprogramming Ability of Antifolates Reveals Soluble CD14 as a Potential Biomarker for Methotrexate Response in Rheumatoid Arthritis

Abstract: The identification of “trained immunity/tolerance” in myeloid cells has changed our perception of the performance of monocytes and macrophages during inflammatory and immune responses. Pemetrexed (PMX) and methotrexate (MTX) are blockers of the one-carbon metabolism (OCM) and commonly used therapeutic agents in cancer and rheumatoid arthritis (RA). We have previously showed that MTX promotes trained immunity in human macrophages. In the present manuscript, we have assessed the anti-inflammatory effects of PMX … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
2
7
0
Order By: Relevance
“…PMX was originally developed to overcome MTX resistance in cancer chemotherapy (55) by harboring more efficient transport properties via RFC, PCFT and FR than MTX (Figure 1C). PMX has shown anti-arthritic effects by suppressing cytokine production in activated T cells of RA patients (75), experimental arthritis models (74) and polarized macrophages in vitro (28). Together, these preclinical studies demonstrate the suitability and feasibility of macrophage PET with [ 18 F]fluoro-PEG-folate for arthritis disease monitoring and therapy response monitoring thereby supporting clinical studies in RA.…”
Section: Frb-targeted Macrophage Pet Imaging In Arthritic Ratsmentioning
confidence: 73%
See 2 more Smart Citations
“…PMX was originally developed to overcome MTX resistance in cancer chemotherapy (55) by harboring more efficient transport properties via RFC, PCFT and FR than MTX (Figure 1C). PMX has shown anti-arthritic effects by suppressing cytokine production in activated T cells of RA patients (75), experimental arthritis models (74) and polarized macrophages in vitro (28). Together, these preclinical studies demonstrate the suitability and feasibility of macrophage PET with [ 18 F]fluoro-PEG-folate for arthritis disease monitoring and therapy response monitoring thereby supporting clinical studies in RA.…”
Section: Frb-targeted Macrophage Pet Imaging In Arthritic Ratsmentioning
confidence: 73%
“…Also FRb functions as one of three transport proteins for folates and antifolates, the two others are the reduced folate carrier (RFC, SLC19A1) and proton-coupled folate transporter (PCFT, SLC46A1) (57) (Figure 1E). The expression of these 3 folate transporters does vary between polarized macrophages; in ex vivo skewed monocytes to M1-type macrophages by GM-CSF and M2-type macrophage by M-CSF, RFC gene expression is differentially higher in M1-type macrophages, whereas FRb and PCFT expression are markedly higher in M2-type macrophages (27,28). Given that FRa/b also retain a high affinity binding profile for folate conjugates, this allowed the design of folate conjugates which could serve as folate based imaging agents like [ 18 F]fluoro-PEG-folate (Figure 1F) (58-60).…”
Section: Folate Receptors: Function Structure and Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from it, leflunomide also favored renal function, especially regarding 24-h proteinuria and serum creatinine[ 26 ]. Methotrexate is a kind of antifolate that inhibit nucleotide synthesis and DNA replication and is commonly used in rheumatoid arthritis treatment[ 27 ]. A meta-analysis indicated that methotrexate was also effective in reducing SLEDAI score and alleviating active arthritis and cutaneous manifestations[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of CD14 in patients associates with higher levels of cholesterol coupled with greater risks of myocardial infarction and cardiovascular‐associated death [71]. CD14 also appears to enhance the severity of cardiomyopathic conditions that result from third degree burn injury [72] and Chagas disease [73]. Finally, CD14 levels have been suggested to predict patient outcomes following acute myocardial infarction [74].…”
Section: Cd14 In Human Diseasesmentioning
confidence: 99%